1990
DOI: 10.1007/bf00204896
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of HLA class I genes by interferon

Abstract: Allele-specific differences in the regulation of HLA class I genes by type I interferon (IFN) were observed after transfection of eight HLA-B, -A, or -C genes into mouse L cells. HLA-B7 and -Bw64 gene expression was significantly more inducible by type I IFN than the genes coding for HLA-B27, HLA-B51, HLA-B38, HLA-B39, HLA-Cw3, and HLA-A2 antigens. Modification of the 5' end of HLA-B7 and HLA-B27 genes revealed the presence of enhancer sequences responding to IFN treatment in the 5' untranslated region of HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Therefore, HLA-B7 transgenes with 0.66 kb of 5' DNA that were used in our previous studies and found to be expressed appropriately in transgenic animals contained all three of these elements. Additional transfection studies have suggested that regulatory elements also lie 3' to the transcription start site (14,23,33,44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, HLA-B7 transgenes with 0.66 kb of 5' DNA that were used in our previous studies and found to be expressed appropriately in transgenic animals contained all three of these elements. Additional transfection studies have suggested that regulatory elements also lie 3' to the transcription start site (14,23,33,44).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies indicate the possibility that regulatory mechanisms involving sequences 3' of the transcription start site also exist (14,23,33,44). Adjacent to one of the enhancers in the 5'-flanking region (enhancer A [20,21] or class I regulatory element [CRE] [7,35]) is a sequence of about 30 bp (the IFN response/consensus sequence [IRS/ ICS]) which was initially identified as being conserved among a number of genes inducible by IFN-ot (13).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Therefore, it is possible that the IRE functions by enhancing splicing efficiency at the terminal 3Ј splice site, enhancing nuclear to cytoplasmic RNA transport, or by stabilizing nuclear pre-mRNA. The splice junction contained within the 3Ј IRE contains a 5Ј polypyrimidine tract flanking the splice acceptor site (52) and a potential purine-rich exonic splicing enhancer (53,54), raising the possibility that the IRE functions to enhance splicing of the terminal 3Ј exon and, in turn, facilitates nuclear-cytoplasmic mRNA transport (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Other class I genes, such as HLA-B7 and the murine H-2L and H-2K genes, have been shown to have a functional ISRE region which, by itself, can mediate a strong transcriptional response to IFN-␥ most likely involving the Janus kinase (Jak)/Stat family of protein kinases (18,57). In addition, transcription of the class Ib gene HLA-E has been shown to be stimulated by IFN-␥ through a unique IFN response element, the interferon response region, through the Jak/Stat pathway (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of these were found to contain the identical sequence that serves as a target for H-2 BF1 and activates transcription in the mouse; five of these have been shown to be functional (Table I). Of the 11 that do not contain the sequence, two are pseudogenes (38 -40), two are HLA-A genes (41,42), two are non-HLA-A/B/C genes that resemble the H-2 TLa/Qa genes of the mouse (43,44), and the final five have been shown to be functional class I genes (45)(46)(47). The isolates of HLA-E and HLA-Aw24 are apparently functional in the thymus (42,43).…”
Section: The H-2 Bf1 Binding Site Is Present 5ј Of Mhc Class I Genes mentioning
confidence: 99%